Optimalisasi Pemanfaatan Media Sosial dalam Upaya Meningkatkan Pengunjung - Hudan Muhamad Muchlis; Indri Rachmawati (UNISBA Press, 2023)
Abstract. Daarus Sunnah Horse Stable is a Horse Stable that breathes Islam in the city of Bandung. Along with the rapid development of information technology, now social media has become a basic need for everyone. Therefore, to increase visitors to the horse stables, Daarus Sunnah carries out marketing activities through Instagram content. The researchers formulated the problem formulation as follows: Why does the Daarus Sunnah horse stable use Instagram social media in conveying information, what is the strategy for using social media in an effort to increase visitors and what are the obstacles faced by the Daarus Sunnah horse stable when carrying out the strategy of using social media. This study aims to answer the formulation of the problem. The research method used is a qualitative analytical descriptive method. The data sources used were primary data, namely data obtained directly from visitors to the stables of Daarus Sunnah and administrators of the stables of Daarus Sunnah through interviews and secondary data, namely through literature studies related to the object under study. Based on the research results, the conclusions obtained are that the reasons for using Instagram content include market needs, effective media and also as a means of branding. The content creation process begins with the planning, uploading, and finally evaluation stages. As for the obstacles in the process, there are no experts, no special budget for advertising costs and limited content creation equipment. Keywords: Marketing Communications, Instagram, Horses Abstrak. Istal Kuda Daarus Sunnah adalah Istal Kuda yang bernafaskan Islam di kota Bandung. Seiring dengan berkembang pesatnya teknologi Informasi sekarang media social sudah menajdi kebutuhan pokok bagi semua orang. Maka dari itu untuk meningkatkan pengunjung istal kuda Daarus Sunnah melakukan kegiatan pemasarannya melalui konten-konten Instagram. Adapun peneliti merumuskan rumusan masalah sebagai berikut: Mengapa istal kuda Daarus Sunnah menggunakan media sosial Instagram dalam menyampaikan informasi, bagaimana strategi pemanfaatan media sosial dalam upaya meningkatkan pengunjung dan bagaimana hambatan yang dihadapi istal kuda Daarus Sunnah ketika menjalankan strategi pemanfaatan media sosial. Penelitian ini bertujuan untuk menjawab rumusan masalah tersebut. Metode penelitian yang digunakan adalah metode deskriptif analitis secara kualitatif. Sumber data yang digunakan data primer yaitu data yang diperoleh langsung dari pengunjung istal kuda Daarus Sunnah dan Pengurus istal kuda Daarus Sunnah melalui wawancara dan data sekunder yaitu melalui studi kepustakaan yang berhubungan dengan objek yang diteliti. Berdasarkan hasil penelitian, Simpulan yang diperoleh yaitu alasan penggunaan konten Instagram diantaranya karena kebutuhan pasar, media yang efektif dan juga sebagai sarana branding. Dalam proses pembuatan kontennya dimulai dengan tahap proses perencanaan, uploading, dan terakhir evaluasi. Adapun yang menjadi kendala dalam prosesnya yaitu tidak ada tenaga ahli, tidak ada anggaran khusus untuk biaya iklan dan terbatasnya peralatan pembuatan konten.. Kata Kunci: Komunikasi Pemasaran, Instagram, Kuda